Experiment on Seepage Property and Sand Inrush Criterion for Granular Rock Mass. (2nd November 2017) - Zhang, Kai; Zhang, Boyang; Liu, Jiangfeng; Ma, Dan; Bai, Haibo
Abstract : Water and sand inrush is one of the most serious threats in some shallow coal mines in China. In order to understand the process of sand inrush, experiments were performed to obtain the criterion for sand inrush. First, seepage tests were carried out to study the hydraulic properties of granular sandstone. The results indicate that seepage velocity has a linear relation with the porosity and particle-size distribution parameter. Then, sand inrush tests were conducted to investigate the critical conditions for sand inrush occurrence. It is determined that the sand inrush zone can be clearly distinguished based on the values of porosity and particle-size distribution parameter. Additionally, sand inrush tended to happen in the conditions of high porosity, high seepage velocity, and large particle-size distribution parameter. Further, general principles for preventing the water and sand inrush were proposed, such as reducing the porosity, improving the pore structure, and decreasing the seepage velocity. The proposed principles have been successfully used in situ to control the water and sand inrush.